OC-051 Patients Undergoing Radiofrequency Ablation (Rfa) for Barrett'S Related Neoplasia have Improved outcomes with Decreasing Lenghths of Baseline Barrett'S Oesophagus (Be) & Increasing Number of RFA Sessions. (4th June 2013) - Haidry, R; Banks, M; Butt, M; Gupta, A; Dunn, J; Smart, H L; Bhandari, P; Smith, L-A; Willert, R; Fullarton, G; Pietro, M di; Penman, I; et al.
Abstract : Introduction: BE is the pre-cursor to oesophageal adenocarcinoma (OAC). High grade dysplasia (HGD) & early mucosal neoplasia in BE have a 40–60% risk of progressing to OAC. Endoscopic mucosal resection (EMR) & RFA are alternatives to surgery for curative treatment of these patients. We present prospective data from 19 centres in the UK HALO RFA registry. Methods: Before RFA, superficial lesions were removed by EMR. Patients then underwent RFA 3 monthly until all BE was ablated or cancer developed (endpoints). Biopsies were taken at 12 months for Primary outcomes (clearance for HGD (CR-HGD), all dysplasia (CR-D) & BE (CR-BE)). Results: 630 patients have outcomes recorded. We report on 370 who have completed treatment. 81% male, mean age 68 years (40–91). Patient's underwent mean 2.5 ablations (1–6) during protocol. 70% baseline histology HGD, 27% IMC & 3% LGD. Mean length baseline BE 5.6cm (1–20). At 12 months CR-HGD was 87% patients, CR-D 82%, & CR-BE 64%. 97% with no dysplasia at 12 months remain disease free at most recent follow up (median 18 months, range 2–68). Kaplan Meier statistics predict CR-D is durable at 5 years with 88% remaining disease free. Logistic regression demonstrate each extra 1 cm of BE reduces chances of attaining CR-D by 15.7% (OR 1.156, SE 0.048, CI 1.07–1.26, p = 0.0003) & for each extra RFA treatment likelihood of CR-D increases by 31.7% (OR = 0.683, SE 0.95, CI 0.52–0.89, p = 0.0006). Progression to invasive cancer at 12 months is 2.7%. Symptomatic strictures requiring dilatation occurred in 9% after treatment. Conclusion: End of protocol CR-D is encouraging at 83% & successful eradication appears durable. Patients with shorter segment BE respond better & multiple treatments are more likely to achieve CR-D. Our data represent real life outcomes of integrating novel endotherapy into demanding endoscopy service commitments Disclosure of Interest: None Declared